Central bank forecasting: A survey - Carola Conces Binder; Rodrigo Sekkel (Bank of Canada, 2023)
Central banks' forecasts are important monetary policy inputs and tools for central bank communication. We survey the literature on forecasting at the Federal Reserve, European Central Bank, Bank of England and Bank of Canada, focusing especially on recent developments. After describing these central banks' forecasting frameworks, we discuss the literature on central bank forecast evaluation and new tests of unbiasedness and efficiency. We also discuss evidence of central banks' informational advantage over private sector forecasters-which appears to have weakened over time-and how central bank forecasts may affect private sector expectations even in the absence of an informational advantage. We discuss how the Great Recession led central banks to evaluate their forecasting frameworks and how the COVID-19 pandemic has further challenged central bank forecasting. Finally, we consider directions for future research.
Keywords: E47; E52; E58; 330; Monetary policy